2017
DOI: 10.1038/s41598-017-02416-6
|View full text |Cite
|
Sign up to set email alerts
|

Scopolin ameliorates high-fat diet induced hepatic steatosis in mice: potential involvement of SIRT1-mediated signaling cascades in the liver

Abstract: The present study aimed to investigate whether scopolin exhibits beneficial effects on high-fat diet (HFD)-induced hepatic steatosis in mice. The involvement of sirtuin 1 (SIRT1) as a molecular target for scopolin was also explored. Scopolin decreased the Km of SIRT1 for p53 and nicotinamide adenine dinucleotide without altering Vmax in a cell-free system. Scopolin alleviated oleic acid-induced lipid accumulation and downregulation of SIRT1 activity in HepG2 cells, and these beneficial effects of scopolin were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…[ 27 ]. Data from our laboratory have shown that 0.02% ( w / w ) scopolin supplemented to HFD mice significantly prevented increments in body weight, and hepatic lipids levels [ 28 ]. Scopolin (100 mg·kg −1 body weight) ameliorated adjuvant-induced arthritis in rats by the downregulation of proinflammatory and proangiogenic cytokines, such as vascular endothelial growth factor, basic fibroblast growth factor-2, and interleukin-6 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ]. Data from our laboratory have shown that 0.02% ( w / w ) scopolin supplemented to HFD mice significantly prevented increments in body weight, and hepatic lipids levels [ 28 ]. Scopolin (100 mg·kg −1 body weight) ameliorated adjuvant-induced arthritis in rats by the downregulation of proinflammatory and proangiogenic cytokines, such as vascular endothelial growth factor, basic fibroblast growth factor-2, and interleukin-6 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, mice and rats suffering from ischaemia, sepsis, or chronic obstructive pulmonary disease were treated with several natural products including melatonin 76,[87][88][89] , diallyl trisulphide 90 , and punicalagin 86 . Other examples include the effects of ghrelin 82,84 , hydrogen-rich saline 83 , carbon monoxide 62 , the SIRT1 activators resveratrol 67,79,91 and scopolin 92 , and the PARP inhibitor 3aminobenzamide 36 . In all these cases, EX-527 was used as a pharmacological tool to demonstrate that SIRT1 activation was involved in the beneficial effects of the compounds under study.…”
Section: In Vivo Assays Of Ex-527mentioning
confidence: 99%
“…Liver specific deletion of SIRT-1 contributes to increased inflammation, endoplasmic reticulum stress and hepatic steatosis ( Purushotham et al, 2009 ). While SIRT-1 over-expression or activation promotes lipolysis, fat loss and remarkably protects high-fat diet induced obese mice from liver steatosis ( Pfluger et al, 2008 ; Yoo et al, 2017 ). Previous reports indicate that many natural products exert regulatory effects on liver lipid metabolism through activation of SIRT-1, among which are resveratrol ( Ahn et al, 2008 ), alpha-lipoic acid ( Chen et al, 2012 ), troxerutin ( Zhang et al, 2014 ), and salvianolic acid B ( Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%